PERAN KOMUNIKASI INTRAPERSONAL DALAM MENGATASI TINDAKAN SELF-HARM PADA MAHASISWA DI KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
This study has two objectives, namely: First, to find out the factors that cause self-harm in students in the city of Makassar. Second, the role of intrapersonal communication in overcoming self-harm actions committed by students in Makassar City. The informant is the perpetrator of self-harm, which was obtained using the snowball sampling technique so that the researcher obtained four people. The type of research used is qualitative research with a phenomenological approach, using two data sources, namely primary data and secondary data. The data collection technique was carried out through three methods, namely observation, interview, and documentation. The data processing and analysis techniques are carried out by data reduction techniques, data presentation and conclusion drawn. The results of this study show that: first, self-harm actions carried out by students in Makassar City are caused by various factors such as tension in the family, divorce, academic pressure, parental expectations, competition with friends, and conflicts in romantic relationships, all of which worsen the emotional state. Second, students in Makassar City overcome self-harm with intrapersonal communication such as talking to themselves, introspection, social support, writing, and activities outside the home without involving the closest people to manage negative emotions.